Può esistere una dicotomia natura-cultura nei processi evolutivi del linguaggio? - Antonino Pennisi (Rivista Italiana di Filosofia del Linguaggio)
n this article we suggest a way to settle the classical nature vs nurture debate through a naturalized idea of language’s structures and functions. This idea involves two essential conditions: the first is that we must be able to describe the species-specificity of human language in naturalistic terms; the second is that we must estimate linguistic behaviors on the comparative basis of the adaptive selection, rather than referring only to their functional and social uses in human societies. In other words, if we are able to establish the ethologic species-specificity of language, then the resulting philosophy of language should take into account the “price of language”, that is not only its “inner potentials (traditionally described as “cultural”), but also its high “external” risks (traditionally considered as “natural”). In this work, we use the origin of human language as a way to show that the nature vs nurture debate is unfounded. The balance between what is conveyed by the phylogenetic structure and what is recapped at every ontogenetic restart can be different , but each animal species acquires and conveys data to co-specifics always using dedicated procedures: in biology culture is any mechanism that allows to acquire information from the members of one's own species through social systems. Thus, we can consider culture as an expression of the biological possibilities of Homo sapiens.